Hydrogel preparation and application thereof
By adopting a hydrogel preparation with a dual network structure and combining bionic materials, the problem that existing skin moisturizers are difficult to simulate the human skin moisturizing system, achieving efficient moisturizing and transdermal delivery effects.
Patent Information
- Application Number
- CN202311191123.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-14
AI Technical Summary
Existing skin moisturizers are difficult to effectively simulate the natural moisturizing system of human skin, resulting in dry and desquamation of the skin, and it is difficult to achieve effective transdermal delivery of drugs.
A hydrogel preparation is used, and its components include sodium polyacrylate NP700, carbomer, sodium carboxymethylcellulose, gelatin, sodium hyaluronate, bentonite, glycerol, polyethylene glycol, aluminum glycol and disodium ethylenediaminetetraacetate. Through the combination of a dual network structure and a bionic material, a hydrogel preparation with good moisturizing and drug-carrying properties is formed.
This hydrogel preparation significantly improves the moisturizing properties of the skin, enhances the transdermal delivery efficiency of drugs, and has broad application prospects in skin care products and drug-carrying transdermal products.
Smart Images

Figure CN119606764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogel preparation and application thereof, belonging to the technical field of daily cosmetics. Background Art
[0002] Healthy skin should be smooth, moisturized and elastic, which is largely due to the moisture in the skin. These appearance signs are related to the function of the skin's own moisturizing system. The function of the moisturizing system is to maintain a certain amount of water in the skin and resist damage to the skin caused by internal and external factors such as evaporation, drying, and even cracking.
[0003] The natural moisturizing system in human skin is mainly composed of water, lipids, and natural moisturizing factors. Lipids are layered and filled between keratinocytes. Their main function is to form a water barrier to prevent water loss. When lipids are deficient due to various reasons, their water barrier function is weakened, and water loss through the epidermis will increase, resulting in dry and flaky skin. Natural moisturizing factor is a general term for some low molecular weight substances that can bind to water in the stratum corneum, including amino acids, pyrrolidone carboxylic acid, lactate, urea, amines, uric acid, glucosamine, citrate, sodium, potassium, calcium and magnesium, phosphate, chlorine, sugar, organic acid, peptides and other unknown substances. Natural moisturizing factor accounts for about 10% of the stratum corneum cell matrix. The water bound by natural moisturizing factor is a relatively fixed part of the stratum corneum. The part of water with a larger content change is related to the selective permeability and lipid barrier of the stratum corneum, and the permeability is related to the integrity and characteristics of the lipids and lamellar structure between keratinocytes. The moisture in the stratum corneum of the skin is of great significance to the skin.
[0004] Moisturizers are used to simulate the natural moisturizing system in human skin, which is composed of water, lipids, and natural moisturizing factors. Their function is to delay water loss, increase dermal-epidermal water penetration, temporarily protect the skin, reduce damage, and promote the repair process. Skin moisturizers are composed of main ingredients and other auxiliary ingredients. The main ingredients include occlusive agents, hygroscopic agents, hydrophilic matrix, light-blocking agents, and some special additives, while auxiliary ingredients include emulsifiers, preservatives, fragrances, liposomes, etc.
[0005] To delay skin aging and prevent and treat skin diseases, skin moisturizing is the basis, and vigorously developing skin moisturizers with significant moisturizing effects is the first priority. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a hydrogel preparation and application thereof.
[0007] The technical solution of the present invention is as follows:
[0008] A hydrogel preparation comprises the following components, all in percentage by mass: 6.5-7% sodium polyacrylate NP700, 0.35-0.45% carbomer, 2-3% sodium carboxymethyl cellulose, 0.8-1.2% gelatin, 0.4-0.5% sodium hyaluronate, 1.0-1.4% bentonite, 30-32% glycerol, 2-5% polyethylene glycol, 0.9-1.1% aluminum glycolate, 1.5-1.7% disodium edetate, and deionized water to 100%.
[0009] Preferably, according to the present invention, the components of the hydrogel preparation are: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1.2%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium edetate 1.6%, and deionized water is supplemented to 100%.
[0010] Preferably according to the present invention, the hydrogel preparation further comprises a transdermal short peptide Ser-Cys-Arg.
[0011] Further preferably, the content of the transdermal short peptide in the hydrogel preparation is 0.08%.
[0012] The preparation method of the above hydrogel preparation comprises the following steps:
[0013] Sodium polyacrylate NP700, sodium carboxymethyl cellulose and carbomer are dispersed in an appropriate amount of glycerol, and then deionized water is added and stirred at 50±2°C to obtain colloid liquid A; then the remaining glycerol, sodium hyaluronate, gelatin, polyethylene glycol, bentonite and aluminum glycolate are added to the above colloid liquid A in sequence, and the suspension B is obtained after stirring; after the suspension B is stable, disodium ethylenediaminetetraacetate is added; and the pH of the obtained paste matrix is adjusted to 6.5±0.1 with triethanolamine, and the mixture is aged in a constant temperature box at 40±2°C for 20-30min, and then placed at room temperature for 40-50h to obtain the finished product.
[0014] The preparation method of the above-mentioned hydrogel preparation containing transdermal short peptides comprises the following steps:
[0015] Sodium polyacrylate NP700, sodium carboxymethyl cellulose and carbomer are dispersed in an appropriate amount of glycerol, and then deionized water is added, and the mixture is stirred evenly at 50±2°C to obtain colloid liquid A; then the remaining glycerol, sodium hyaluronate, gelatin, polyethylene glycol, bentonite and aluminum glycolate are added to the above colloid liquid A in sequence, and the mixture is stirred evenly to obtain suspension B; after the suspension B is stable, disodium ethylenediaminetetraacetic acid is added; transdermal short peptides are added under low-speed stirring, and the pH of the obtained paste matrix is adjusted to 6.5±0.1 with triethanolamine, and the mixture is aged in a constant temperature box at 40±2°C for 20-30min, and then placed at room temperature for 40-50h to obtain the finished product.
[0016] Application of the above hydrogel preparation in the preparation of cosmetic products.
[0017] Preferably according to the present invention, the beauty products include skin care products and cosmetics.
[0018] Application of the above hydrogel preparation in the preparation of drug-carrying transdermal products.
[0019] Preferably, according to the present invention, the drug-carrying transdermal product further contains at least one active pharmaceutical ingredient in an effective dose for treating a disease.
[0020] Beneficial effects:
[0021] The present invention provides a hydrogel preparation, the components of which include: sodium polyacrylate NP700, carbomer, sodium carboxymethyl cellulose, gelatin, sodium hyaluronate, bentonite, glycerol, deionized water, polyethylene glycol, aluminum glycolate, and disodium ethylenediaminetetraacetate. The hydrogel preparation has good moisturizing properties and can be used for the preparation of skin care products and cosmetics; it also has good drug loading and release properties, especially when a transdermal short peptide is added to the hydrogel preparation, the transdermal effect of the drug can be further promoted, and it has broad application prospects in the preparation of drug-loaded transdermal products. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the cross-linked structure of the hydrogel preparation.
[0023] Figure 2 The figure is a bar graph showing the adhesion strength of hydrogel preparations with different dosages of the components.
[0024] Figure 3 It is a bar graph of the moisturizing rate of hydrogel preparations with different dosages of ingredients.
[0025] Figure 4 It is a bar graph of the air permeability of hydrogel preparations with different bentonite dosages.
[0026] Figure 5 This is the bonding strength curve of the hydrogel preparation at different aluminum glycolate dosages.
[0027] Figure 6 The viscosity curves of hydrogel preparations at different disodium EDTA concentrations.
[0028] Figure 7 SEM images of different hydrogel preparations.
[0029] Figure 8 This is an electron microscope photograph of a hydrogel preparation loaded with diclofenac sodium drug molecules.
[0030] Fig. 9 This is the cumulative drug release curve of the drug-loaded hydrogel preparation.
[0031] Fig.10 The configurations of six transdermal short peptides in the gas phase.
[0032] Fig.11 The configurations of six transdermal short peptides in liquid phase.
[0033] Fig.12 Schematic diagram of the Franz diffusion cell.
[0034] Fig.13 This is the cumulative permeation curve of diclofenac sodium per unit area in different hydrogel preparation treatment groups. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention is further described below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto. The drugs and reagents involved in the embodiments are all common commercially available products unless otherwise specified; the experimental steps involved in the embodiments are all conventional technical operations in the art unless otherwise specified. The percentages involved in the embodiments are all mass percentages unless otherwise specified.
[0036] The present invention designs and prepares a hydrogel preparation with a double network and bionic structure, studies the interaction between the component ratio and efficacy of the hydrogel, explores the dispersibility and crystallinity of drug molecules in the hydrogel, studies the controlled release rate of active ingredients, and improves the transdermal delivery rate; studies the air permeability, water retention, spreadability, skin adhesion, etc. of the hydrogel. Compared with existing products on the market, the above performances are equal to or better than existing products.
[0037] The components of the hydrogel preparation of the present invention include: sodium polyacrylate NP700, carbomer, sodium carboxymethyl cellulose, gelatin, sodium hyaluronate, bentonite, glycerol, deionized water, polyethylene glycol, aluminum glycolate, and disodium ethylenediaminetetraacetate.
[0038] The preparation method of the hydrogel preparation of the present invention comprises the following steps: adding sodium polyacrylate NP700, sodium carboxymethyl cellulose and carbomer to an appropriate amount of glycerol for dispersion, then adding deionized water, stirring evenly at 50°C to obtain a colloid A liquid; then sequentially adding the remaining glycerol, sodium hyaluronate, gelatin, polyethylene glycol, bentonite and aluminum glycolate to the colloid A liquid, stirring evenly to obtain a suspension B; adding disodium ethylenediaminetetraacetate after the suspension B is stable; adjusting the pH of the obtained paste matrix to 6.5 with triethanolamine under low-speed stirring, ripening in a constant temperature box at 40°C for 20 minutes, and then placing at room temperature for 48 hours to obtain a finished hydrogel preparation.
[0039] The components of the hydrogel preparation, such as sodium polyacrylate NP700 (PAA-Na), carbomer (CP), sodium carboxymethyl cellulose (CMC-Na), and gelatin (G), contain a large number of polar groups such as -COOH and -OH. These polar groups can form dense hydrogen bonds with polar groups on the surface of skin tissue. The formation of these hydrogen bonds is expected to enhance the tissue adhesion performance of the hydrogel preparation. The cross-linking schematic diagram of the hydrogel preparation of the present invention is shown in FIG. Figure 1 As shown. -COONa in sodium polyacrylate NP700, -COOH in carbomer, -COONa and -OH in sodium carboxymethyl cellulose, -COOH, -OH, -NH2 in gelatin can react with Al 3+ (Aluminum glycolate will release Al after dissolution 3+ ) chemically cross-linked to form an ion complex network structure. In addition, a large amount of -OH in gelatin, sodium hyaluronate, and sodium carboxymethyl cellulose can form an intermolecular hydrogen bond network with -COOH, -CONH, and NH2. Combining the two cross-linking effects, a hydrogel preparation with a double network structure is formed.
[0040] In addition, sodium hyaluronate is an inherent component of the human body. It is a species-free glucuronic acid that is distributed in the cytoplasm and interstitium of cells, lubricating and nourishing cells and their organs, and providing a microenvironment for cell metabolism. It can absorb water five hundred times its own weight and has extremely strong moisturizing properties. In addition, exogenous small molecule sodium hyaluronate will also penetrate into the epidermis, promoting the supply of skin nutrition and the excretion of waste. Gelatin is a peptide molecule polymer substance, a type of protein obtained by partial hydrolysis of collagen. Gelatin is a natural polymer material with a structure similar to that of biological tissues. It has good biocompatibility and antioxidant capacity. In addition, gelatin also absorbs a large amount of water to form a gel, which has good moisturizing properties. With the addition of two bionic materials, hydrogel preparations are expected to promote the increase of skin water content, improve the nutritional status of the skin, and improve the penetration efficiency of drug molecules.
[0041] The sources and specifications of the raw materials in the examples are shown in Table 1.
[0042] Table 1. Specifications and manufacturers of each component raw material
[0043]
[0044] Example 1: Adhesion Study
[0045] A single factor experiment was conducted on the components that have a greater impact on the gel adhesion in the hydrogel preparation. The specific experimental method is as follows:
[0046] Single factor experiment of sodium polyacrylate NP700: The proportion of sodium polyacrylate NP700 was set to 6.5%, 7.0%, 7.5%, 8.0%, and 8.5%, respectively, and the proportions of the other components were: carbomer 0.35%, sodium carboxymethyl cellulose 2%, gelatin 0.8%, sodium hyaluronate 0.2%, bentonite 1%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the adhesion performance of the hydrogel preparation was tested.
[0047] Single factor experiment of sodium carboxymethyl cellulose: The proportion of sodium carboxymethyl cellulose was set to 1%, 2%, 3%, 4%, and 5%, respectively, and the proportions of the other components were: sodium polyacrylate NP700 7%, carbomer 0.35%, gelatin 0.8%, sodium hyaluronate 0.2%, bentonite 1%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the adhesion performance of the hydrogel preparation was tested.
[0048] Single factor experiment of carbomer: The proportion of carbomer was set to 0.25%, 0.35%, 0.45%, 0.55%, and 0.65%, respectively, and the proportions of the other components were: sodium polyacrylate NP700 7%, sodium carboxymethyl cellulose 3%, gelatin 0.8%, sodium hyaluronate 0.2%, bentonite 1%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the adhesion performance of the hydrogel preparation was tested.
[0049] Single factor experiment of gelatin: The proportion of gelatin components was set to 0.8%, 1.2%, 1.6%, 2.0%, and 2.4%, respectively, and the proportions of the other components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, sodium hyaluronate 0.2%, bentonite 1%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium edetate 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the adhesion performance of the hydrogel preparation was tested.
[0050] The adhesion performance of the hydrogel preparation was tested using an electronic universal testing machine. Fresh pig skin purchased from a supermarket was cut into a rectangle of 4.0 cm × 1.0 cm × 0.2 cm. After the preparation was completed, the pig skin was placed on a thermostat. After the temperature of the pig skin was constant at 36.5 ± 0.5 ° C, the hydrogel preparation was evenly applied to the opposite sides of the two pieces of pig skin, with a contact area of 1.0 × 1.0 cm 2 The weight sensor is 200N and the crosshead speed is 5mm / min.
[0051] The bonding strength is calculated as follows:
[0052]
[0053] Where: P is the bonding strength (KPa), F is the tensile stress (N), S is the contact area (cm 2 ).
[0054] The results of the test are as follows Figure 2 As shown in the figure, sodium polyacrylate NP700, as the skeleton support material of the hydrogel, will chemically cross-link with aluminum glycolate to solidify the matrix. When its dosage is 6.5%-7%, the bonding strength continues to increase. This is because the polymer material itself has viscosity, and as the dosage increases, the degree of cross-linking increases. When the dosage of sodium polyacrylate NP700 is greater than 7%,
[0055] Excessive cross-linking, where the number of cross-linking points exceeds the optimal number, the cross-linking spacing becomes shorter, and a considerable portion of the chain segments are bound inside the cross-linking grid and are difficult to stretch freely. This also leads to increased rigidity of the matrix and decreased adhesion. When the dosage of sodium polyacrylate NP700 is between 6.5% and 7%, the spreadability is better.
[0056] Carbomer is a good thickener, which contains a large number of carboxyl groups, and can cross-link with aluminum ions (aluminum glycolate will release aluminum ions after dissolution) to enhance the cohesion of the matrix. When the amount of carbomer exceeds 0.45%, the rigidity of the matrix is enhanced and the adhesion is reduced due to the large amount of carboxyl groups added. When the amount of carbomer is between 0.45% and 0.65%, the spreadability of the hydrogel preparation is better.
[0057] Sodium carboxymethyl cellulose is used as a thickener for the matrix. When the dosage is between 2% and 5%, the bonding strength increases continuously. This is because COO - The introduction of sodium carboxymethyl cellulose will increase the wettability of the matrix to the adhered object, so the adhesion will increase. However, when the dosage exceeds 5%, the rigid components in the matrix components will decrease relatively, the cohesion will decrease, and the bonding strength will decrease. When sodium carboxymethyl cellulose exceeds 3%, the spreadability is very poor and it is difficult to coat.
[0058] Gelatin is a good adhesive. The bonding strength of the matrix increases with the increase of its dosage. However, its spreadability decreases when its dosage exceeds 1.2%.
[0059] Example 2: Moisture Retention Study
[0060] The high water content of hydrogel is its basic characteristic. The high water content makes the hydrogel hydrated to a high degree, but the water is easy to lose, especially during storage, it is very important to keep the water. Once the original high water content structure in the hydrogel changes, the stability and balance of the hydrogel will be destroyed, and the basic properties of the hydrogel such as adhesion, cohesion and other parameters will also change. Therefore, a suitable moisturizer must be added to the hydrogel preparation to keep the water and prevent water loss. The present invention selects glycerol and sodium hyaluronate as moisturizers.
[0061] A single factor experiment was conducted on the moisturizing components in the hydrogel preparation. The specific experimental method is as follows:
[0062] Single factor experiment of sodium hyaluronate: The proportion of sodium hyaluronate was set to 0.4%, 0.5%, 0.6%, 0.7%, and 0.8%, respectively, and the proportions of the other components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, bentonite 1%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium edetate 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the moisturizing performance of the hydrogel preparation was tested.
[0063] Single factor experiment of glycerol: The proportion of glycerol was set to 27%, 28%, 29%, 30%, 31%, and 32%, respectively, and the proportions of the remaining components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium edetate 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the moisturizing performance of the hydrogel preparation was tested.
[0064] The above hydrogel preparations were coated on glass plates at a coating amount of 10 mg / cm 2 , weigh the glass plate containing the hydrogel preparation, and then put it into a 37°C constant temperature box. After leaving it for 1 hour, take it out and weigh it. Calculate the moisturizing rate of each group according to the following formula.
[0065]
[0066] Where: M: Moisture retention rate (%),
[0067] M1: mass of the hydrogel preparation before placement, g,
[0068] M2: mass of the hydrogel preparation after placement, g,
[0069] M3: initial water content of the hydrogel formulation, g.
[0070] Test results such as Figure 3 As shown, the experimental results show that when the amount of hyaluronic acid in the hydrogel preparation is 0.4%, the moisturizing rate within 1 hour reaches the best; when the amount of glycerol in the hydrogel preparation is 30-32%, the moisturizing rate effect within 1 hour is better.
[0071] Example 3: Air Permeability Study
[0072] A single factor experiment was conducted on the components that have a significant impact on the air permeability of the hydrogel preparation. The specific experimental method is as follows:
[0073] Single factor experiment of bentonite: The proportion of bentonite components was set to 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, and 2.0%, respectively, and the proportions of the remaining components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared and the air permeability of the hydrogel preparation was tested.
[0074] Air permeability test: Place anhydrous CaCl2 in a conical flask, apply the prepared hydrogel preparation evenly on the non-woven fabric, seal it at the mouth of the cup, and measure the weight. Place the conical flask in an environment with a temperature of 37±0.5℃ and a humidity of 80%, and measure the weight after 24 hours. Calculate the 24-hour air permeability according to the following formula:
[0075]
[0076] Where: m is the difference between the two weighings (g), s is the bottle mouth area (cm 2 ), t is the test time (h).
[0077] Test results such as Figure 4 As shown: Bentonite is used as a filler in hydrogel preparations. Its internal reticular structure makes the matrix more breathable. In addition, this reticular structure can also bind a large amount of free water to enhance the moisture retention of the matrix. According to the experimental results, when the amount of bentonite is 1.2%, its air permeability is the best.
[0078] Embodiment 4:
[0079] Single factor experiment of cross-linking agent aluminum glycolate: The component ratio of aluminum glycolate was set to 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%, respectively, and the ratios of the other components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1.2%, glycerol 30%, polyethylene glycol 3%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above component ratios, a hydrogel preparation was prepared and the adhesive strength of the hydrogel preparation was tested.
[0080] The results of the test are as follows Figure 5 As shown in the experimental results, when the amount of aluminum glycolate exceeds 1.1%, the adhesion decreases, which may be due to the Al released by aluminum glycolate. 3+ Excessive cross-linking with sodium polyacrylate NP700 causes excessive cross-linking. Therefore, the optimal dosage of aluminum glycolate is about 1.1%.
[0081] Embodiment 5:
[0082] Generally speaking, there are two types of cross-linking regulators, one is a pH cross-linking regulator (citric acid, tartaric acid), and the other is a chelating agent EDTA. However, since carbomer and sodium polyacrylate NP700 are selected in the hydrogel preparation of the present invention, which contain a large number of carboxyl groups, the dispersion itself is weakly acidic, and the pH cross-linking regulator cannot play its own function of adjusting pH, so a single factor experiment is performed on the chelating agent EDTA.
[0083] Single factor experiment of EDTA-2Na: The proportion of disodium ethylenediaminetetraacetate (EDTA-2Na) was set to 1.5%, 1.6%, 1.7%, 1.8%, and 2.0%, respectively, and the proportions of the remaining components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1.2%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, and deionized water was supplemented to 100%. A hydrogel preparation was prepared according to the above proportions, and the viscosity of the hydrogel preparation was tested using a viscometer.
[0084] The experimental results are as follows Figure 6 As shown, according to the experimental results, when the amount of disodium edetate increases, the viscosity after complete cross-linking gradually decreases, that is, the degree of cross-linking decreases. According to the viscosity, the amount of disodium edetate can be selected to be 1.5-1.7%.
[0085] Embodiment 6:
[0086] During the preparation of the hydrogel matrix, bubbles are easily generated, which will affect the adhesion and drug release properties of the hydrogel. In order to eliminate the influence of bubbles, polyethylene glycol (PEG) is selected as a defoaming agent for the gel matrix.
[0087] Single factor experiment of polyethylene glycol: The proportion of polyethylene glycol was set to 1%, 2%, 3%, 4%, and 5%, respectively, and the proportions of the other components were: sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1.2%, glycerol 30%, aluminum glycolate 1.1%, disodium ethylenediaminetetraacetic acid 1.6%, and deionized water was added to 100%. According to the above proportions, a hydrogel preparation was prepared, and the defoaming performance during the preparation of the hydrogel preparation was tested.
[0088] Evaluation standard of defoaming performance: Calculate the defoaming performance of hydrogel preparations at 1 cm 3 The number of bubbles in the sample is averaged. The fewer the number of bubbles, the better the defoaming performance. When the number of bubbles is 0-2, it is excellent, recorded as ++++; when the number of bubbles is 3-4, it is good, recorded as +++; when the number of bubbles is 5-6, it is relatively poor, recorded as ++; when the number of bubbles is greater than 6, it is poor, recorded as +.
[0089] The defoaming performance evaluation criteria are shown in the following table:
[0090] Table 2 Evaluation criteria for defoaming performance of defoaming agents
[0091]
[0092] The experimental results are shown in the following table:
[0093] Table 3. Defoaming performance evaluation results at different polyethylene glycol dosages
[0094] Final PEG concentration 1% 2% 3% 4% 5% Defoaming performance ++ +++ ++++ ++++ +++
[0095] According to the experimental results, the optimal dosage of defoaming agent polyethylene glycol is 3%.
[0096] According to the above experimental results, the optimal formula of the hydrogel preparation is sodium polyacrylate NP700 7%, carbomer 0.45%, sodium carboxymethyl cellulose 3%, gelatin 1.2%, sodium hyaluronate 0.4%, bentonite 1.2%, glycerol 30%, polyethylene glycol 3%, aluminum glycolate 1.1%, disodium edetate 1.6%, and deionized water is supplemented to 100%.
[0097] Example 7: Structure of hydrogel formulation
[0098] The network structure of the hydrogel preparation was observed by SEM. The hydrogel preparation was prepared according to the best formula of Example 6 and was recorded as PAA-G-HA-CP-CMC-Na-Al 3+ The hydrogel formulation without carbomer, sodium carboxymethylcellulose and sodium hyaluronate based on the optimal formula is recorded as PAA-Na-G-Al 3+ The hydrogel preparation without carbomer, sodium carboxymethylcellulose, gelatin and sodium hyaluronate based on the optimal formula is recorded as PAA-Na-Al 3+ .
[0099] SEM measurement: The morphology of the hydrogel preparation was observed on a scanning electron microscope at an accelerating voltage of 15 KV. The hydrogel was frozen in liquid nitrogen and freeze-dried at -78 °C for 24 h. After freeze-drying, the samples were cut and sputter-coated with gold and then observed using a scanning electron microscope.
[0100] SEM images are shown in Figure 7 As shown in SEM images, PAA-Na-Al 3+ The pore size of the hydrogel is mostly between 50-100 μm, which is significantly larger than that of PAA-Na-G-Al 3+ Hydrogel; PAA-G-HA-CP-CMC-Na-Al 3+ The pore surface of the hydrogel is relatively smooth, without any granular matter, and the pore size is more regular and the density is higher. This double network structure will improve the mechanical properties of the hydrogel preparation. In addition, the porous structure will also more effectively transport and store drug molecules and oxygen.
[0101] Example 8: Moisturizing performance test of hydrogel preparation
[0102] A hydrogel preparation was prepared according to the optimal formula obtained in Example 6, and the hydrogel preparation was applied to the skin surface of the test subject at a coating amount of 100 mg / cm 2 The subjects' skin was tested for 1-hour transepidermal water loss and 5-hour skin moisture content. The specific test methods are as follows:
[0103] Skin moisture content test: Corneometer CM 828 skin moisture content test probe is used for testing. The probe principle is based on the capacitance method. Experimental method: First, the instrument probe needs to be disinfected with 75% alcohol and the instrument needs to be debugged; open the instrument software, the instrument probe needs to be vertically downward, and then press the probe on the test site on the subject's skin, take three points at the same site, and finally take the average value; measure at 0, 1, 2, 3, 4, and 5 hours after application.
[0104] Transepidermal water loss test: Corneometer TM 300 transepidermal water loss measuring probe is used for testing. Experimental method: First, the instrument probe needs to be disinfected with 75% alcohol and the instrument needs to be debugged; open the instrument software, the instrument probe needs to be vertically downward, and then the probe is pressed on the test site on the subject's skin, three points are taken at the same site, and the average value is finally taken; the measurement is performed at 10, 20, 30, 40, 50, and 60 minutes after application.
[0105] Table 4. 1h transepidermal water loss, TEWL value (g / (cm·h))
[0106] TEWL value 10min 20min 30min 40min 50min 60min Unprocessed 44.9 41.5 42.1 39.9 40.4 42.4 Hydrogel 41.9 37.5 35.3 34.8 32.4 29.4
[0107] Table 5. Skin moisture content within 5 hours (g / m 2 )
[0108] Water content 0h 1h 2h 3h 4h 5h Unprocessed 64.3 66.3 61.1 66.2 63.1 62.1 Hydrogel 62.6 105.6 109.4 99.8 101.4 80.6
[0109] The measurement results are shown in Tables 4 and 5. The results show that after using the hydrogel preparation, the TEWL value and skin moisture content of the skin were measured. The TEWL value decreased by 30.7% at 60 minutes, and the skin moisture content increased by 29.8% at 5 hours.
[0110] Example 9: Drug loading performance of hydrogel formulation
[0111] The hydrogel preparation was prepared according to the optimal formulation of Example 6.
[0112] Preparation of drug-loaded hydrogel preparation: At 37°C, a freeze-dried PAA-G-HA-CP-CMC-Na-Al 3+ The hydrogel (about 0.1 g) was immersed in 100 mL of 0.02 mg / mL diclofenac sodium aqueous solution. After 24 hours, the hydrogel was taken out and the water on the surface of the hydrogel was dried with filter paper to obtain a drug-loaded hydrogel preparation. The ultraviolet absorbance of the diclofenac sodium solution at 275 nm before and after adsorption was measured, and the adsorption amount of the drug diclofenac sodium by the hydrogel preparation was calculated according to the working curve.
[0113] The hydrogel preparation loaded with diclofenac sodium drug molecules was freeze-dried, and then placed on a glass slide to observe its morphology under a microscope.
[0114] The results are as follows Figure 8 As shown, it can be seen that diclofenac sodium is distributed more evenly in the hydrogel preparation without agglomeration, with a high dispersion rate and low crystallinity, which is conducive to the diffusion of drug molecules.
[0115] Drug release performance: In the above hydrogel preparation containing diclofenac sodium drug molecules, diclofenac sodium is released from PAA-G-HA-CP-CMC-Na-Al 3+ The release behavior in the hydrogel was carried out in 100 mL of phosphate buffer solution (pH = 7.4) at 37 ° C and moderate stirring. 2.0 mL of aqueous solution was taken out at intervals, the ultraviolet absorbance at 275 nm was recorded, and the concentration of diclofenac sodium was calculated according to the working curve. In order to eliminate the difference in volume change, 2.0 mL of fresh phosphate buffer solution was added to the system after each sample was taken out. Before the ultraviolet absorbance measurement, the working curve was drawn by measuring the absorbance of diclofenac sodium solutions of different concentrations.
[0116] The cumulative drug release curve of the hydrogel preparation is as follows Fig. 9 As shown, PAA-G-HA-CP-CMC-Na-Al 3+ The hydrogel has a high drug release rate in the initial stage (150 minutes), but the drug release rate gradually reaches a peak within 150 minutes to 350 minutes. Diclofenac sodium has a fast initial release and a long release time, and can be used as an effective matrix for transdermal drug delivery products.
[0117] Example 10: Simulation study on the configuration of transdermal short peptides and their solvation free energy
[0118] The present invention preliminarily uses theoretical calculations to study the primary structures of multiple transdermal short peptides (see Table 6), structures in aqueous solution, and solvation free energy properties (see Table 7). Gaussian16 software was used, density functional theory (DFT) was used, B3LYP / 6-311G** was selected as the calculation level, and the SMD solvent model was used to calculate the primary structures of 6 polypeptides in gas phase and liquid phase. The results are as follows Fig.10 and Fig.11 shown.
[0119] Table 6. Transdermal short peptide numbers and their primary structures
[0120]
[0121] Table 7. Solvation energy and dipole moment of transdermal short peptides
[0122]
[0123] Solvation energy is the energy released during the solvation process of the solvent molecules and the ions dissolved therein to form a complex. This energy is used to destroy the crystal lattice of the electrolyte molecules, allowing them to automatically dissolve in the solvent and become free ions. When the solvation energy is reduced to a level lower than the lattice energy of the electrolyte molecules, the dissolution of the electrolyte molecules in the solvent reaches saturation.
[0124] The dipole moment is the product of the distance between the positive and negative charge centers and the charge carried by the charge centers. It is a vector whose direction is defined as pointing from the positive charge center to the negative charge center. It is represented by the symbol μ and its unit is D (Debye).
[0125] SMD-CDS: Solvation free energy refers to the energy required for the dissolution of organic substances.
[0126] The above research results show that the transdermal short peptide S3 has a low energy and chain extension state in the liquid phase, which is more conducive to its compatibility with other components.
[0127] Example 11: Combination of hydrogel preparation and transdermal short peptide S3
[0128] In vitro percutaneous penetration test:
[0129] This experiment was divided into three groups, namely, transdermal short peptide group, menthol group, and blank control group. The transdermal short peptide group was an experimental group using a drug-loaded hydrogel preparation containing transdermal short peptide S3, the menthol group was an experimental group using a drug-loaded hydrogel preparation containing menthol, and the blank control group was an experimental group using a drug-loaded hydrogel preparation without a permeation enhancer. Menthol, as a widely recognized transdermal penetration enhancer, can destroy the lamellar structure of the stratum corneum and induce lipid cells to form a single-layer vacuolar structure.
[0130] Preparation of drug-loaded hydrogel preparation containing transdermal short peptide S3, according to the best formula of Example 6, adding 1% diclofenac sodium and 0.08% transdermal short peptide at the same time, and supplementing to 100% with deionized water: taking sodium polyacrylate NP700, sodium carboxymethyl cellulose, and carbomer, dispersing in an appropriate amount of glycerin, then adding deionized water, stirring evenly at 50°C to obtain colloid A liquid; adding 1% diclofenac sodium to an appropriate amount of ethanol to dissolve, and then adding the above colloid A liquid. Then, the remaining glycerin, sodium hyaluronate, gelatin, polyethylene glycol, bentonite, and aluminum glycolate are added to the above colloid liquid in sequence, and stirred evenly to obtain suspension B; after suspension B is stable, disodium ethylenediaminetetraacetic acid is added; under low-speed stirring, a corresponding dose of transdermal short peptide is added, and the pH of the obtained paste matrix is adjusted to 6.5 with triethanolamine, and matured in a constant temperature box at 40°C for 20 minutes, and then placed at room temperature for 48 hours to obtain the finished product.
[0131] The preparation of the drug-loaded hydrogel preparation containing menthol was carried out according to the optimal formula of Example 6, and 1% diclofenac sodium and 0.5% menthol were added at the same time, and deionized water was supplemented to 100%. The preparation method was the same as above.
[0132] The preparation of the drug-loaded hydrogel formulation without a penetration enhancer was carried out according to the optimal formulation of Example 6, while adding 1% of diclofenac sodium and supplementing it with deionized water to 100%, and the preparation method was the same as above.
[0133] The Franz diffusion cell used in the experiment is as follows Fig.12 As shown in the figure, the speed of the star-shaped stirrer in the experiment is 500 r / min, the volume of the receiving chamber is 6.5 mL, and the effective diffusion area is 0.785 cm 2 In the experiment, PBS buffer (pH 7.4) was used as the receiving medium and the experiment was carried out in a constant temperature water bath at (32±0.5)℃.
[0134] First, heat the PBS buffer to be used to (32±0.5)℃ and turn on the constant temperature water bath system. Take out the prepared mouse skin, rinse it carefully with PBS buffer, wipe the liquid on the skin surface and place it on the diffusion cell with the mouse skin stratum corneum facing up. After balancing for 30 minutes, discard the receiving solution. Add fresh PBS buffer to the receiving chamber again, place the mouse skin on the diffusion cell, drain the bubbles under the skin, and apply the hydrogel preparation on the mouse skin stratum corneum. Take samples of 200μL at 2, 4, 6, and 8h, and add fresh receiving solution of the same volume and temperature. After filtering the sample through a 0.45μm microporous filter membrane, dilute it to a certain multiple, and determine the concentration of the drug diclofenac sodium using a liquid chromatograph.
[0135] Among them, the cumulative permeability per unit area (Q n ) is calculated by the following formula:
[0136]
[0137] In the formula, Q n is the cumulative permeation per unit area at the nth time point (μg / cm 2 ), C n is the drug concentration measured at the nth time point (μg / mL), V is the volume of the receptor chamber (mL), C i is the drug concentration measured at each sampling (μg / mL), V i is the volume of each sampling (mL), A is the effective diffusion area (cm 2 ).
[0138] The cumulative permeation per unit area of the different hydrogel preparation treatment groups is as follows Fig.13 As shown in the figure, the order of the cumulative permeability per unit area of different groups for 8 hours is: Q 透皮三肽 >Q 薄荷醇 >Q 空白对照组 The cumulative permeation per unit area of the transdermal tripeptide group was significantly higher than that of menthol, and had a significant permeation-enhancing effect.
[0139] Comparative Example:
[0140] (1) Scaffold materials for hydrogel preparations
[0141] Sodium polyacrylate, as the skeleton material of hydrogel preparations, is an important basis for forming a double network structure. Commonly used sodium polyacrylate skeleton materials include: sodium polyacrylate 7S (unneutralized), sodium polyacrylate NP700, and sodium polyacrylate NP800. In sodium polyacrylate NP700, the ratio of polyacrylic acid AA to sodium polyacrylate AANA is the same.
[0142] Sodium polyacrylate 7S, sodium polyacrylate NP700, and sodium polyacrylate NP800 were used as the skeleton materials of the hydrogel preparations, respectively, and the hydrogel preparations were prepared according to the best formula of Example 6. The performance of different skeleton materials was determined by measuring the viscosity of the hydrogel preparations.
[0143] The following table shows the specifications of various types of sodium polyacrylate and the corresponding properties of the prepared hydrogel preparations:
[0144] Table 8. Specifications of various types of sodium polyacrylate and corresponding product properties
[0145]
[0146] Combined with the above table, it can be seen that sodium polyacrylate 7S has a very high pH of 9.1 due to the lack of neutralization, and the crosslinking speed is too fast, the viscosity is low, and it is difficult to control the reaction process. The pH of sodium polyacrylate NP800 is 5.9, the crosslinking speed is too slow, and the viscosity is high, which can easily lead to problems such as slow hydrogel formation and high viscosity. Sodium polyacrylate NP700 has an appropriate pH, moderate crosslinking speed, and moderate viscosity, so it is an ideal material for the skeleton material of hydrogel preparations.
[0147] (2) Cross-linking agents for hydrogel preparations
[0148] The cross-linking agent can chemically cross-link with sodium polyacrylate NP700, carbomer, sodium carboxymethyl cellulose, gelatin, etc. to form an internal network structure of the hydrogel preparation, thereby enhancing its cohesion and formability. The cross-linking agent is generally a high-valent metal ion, such as a soluble aluminum, calcium, etc. compound, and because the soluble aluminum compound can release trivalent aluminum ions to form a more stable spatial network structure, the present invention selects aluminum glycolate, aluminum hydroxide, and aluminum chloride as the cross-linking agent for comparison.
[0149] Aluminum glyoxylate, aluminum hydroxide, and aluminum chloride were used as crosslinking agents for the hydrogel preparations, respectively, and the hydrogel preparations were prepared according to the best formula of Example 6. The performance of different crosslinking agent materials was determined by measuring the crosslinking time of the hydrogel preparations.
[0150] The results are shown in the following table:
[0151] Table 9. Time required for complete crosslinking of hydrogel preparations under different crosslinking agents
[0152]
[0153] As can be seen from the above table, aluminum chloride, as a cross-linking agent, has a short cross-linking time, which easily causes problems such as uneven matrix mixing and low spreadability. However, aluminum hydroxide has a long cross-linking time, which easily causes ointment leakage during the experiment and prolongs the time of the entire experimental process. Aluminum glycolate has a moderate cross-linking time and is more suitable for use as a cross-linking agent for the hydrogel preparation of the present invention.
[0154] (3) Thickening agents for hydrogel preparations
[0155] Although the framework material sodium polyacrylate NP700 has a certain viscosity, it is far from enough for the hydrogel patch. Therefore, it is particularly important to add a suitable viscosity enhancer. In the present invention, the commonly used viscosity enhancers carbomer, gelatin, sodium carboxymethyl cellulose, polyvinyl alcohol, and sodium hydroxypropyl methyl cellulose are selected to investigate the effect on the properties of the hydrogel.
[0156] 1g of sodium polyacrylate was dissolved in deionized water and swelled overnight to prepare a 1% swelling solution. Then, carbomer, gelatin, sodium carboxymethylcellulose, polyvinyl alcohol, and sodium hydroxypropylmethylcellulose were added to the swelling solution, and the concentrations of the above-mentioned thickeners in the swelling solution were 0.3%, 1%, 0.4%, 10%, and 1%, respectively, and the resulting solutions were examined.
[0157] The evaluation index consists of two parts, namely adhesion and film residue, which are graded and scored through observation, with the best rating being excellent and the worst rating being poor. The scoring criteria are shown in the following table.
[0158] Table 10. Scoring criteria for adhesion and film residue
[0159]
[0160] The experimental results are shown in the following table:
[0161] Table 11. Scoring results of adhesion and film residue under different tackifiers
[0162]
[0163] From the analysis of the experimental results, it can be seen that in order to achieve a balance between adhesion and film residue, it is not the best choice to use a single thickener, but a combination of multiple thickeners. Among them, polyvinyl alcohol has a low viscosity and a large dosage, so it is abandoned. Hydroxypropyl methylcellulose sodium cannot be combined with Al 3+ Complexation occurs, so the cohesion of the matrix is low and the formability is poor. Therefore, after comprehensive comparison and analysis, sodium carboxymethyl cellulose, carbomer and gelatin are selected as thickeners.
[0164] (4) Fillers for hydrogel preparations
[0165] Titanium dioxide, bentonite and kaolin were used as fillers for the hydrogel preparation respectively, and the hydrogel preparation was prepared according to the best formula of Example 6. The performance of different filler materials was judged by the granularity and spreadability of the hydrogel preparation.
[0166] The results are as follows:
[0167] Table 12. Granularity and spreadability of hydrogel preparations with different fillers
[0168] Fillers Graininess Spreadability Titanium Dioxide It has a granular feel and is difficult to dissolve completely Poor spreading Bentonite No graininess, delicate skin feel Good spreading Kaolin Slightly grainy Good spreading
[0169] It can be seen from the above table that the hydrogel preparation prepared with bentonite as a filler not only has good spreadability, but also has no granular feel and a delicate skin feel.
Claims
1. A hydrogel preparation, characterized in that: The components are, in percentage by mass, 6.5-7% sodium polyacrylate NP700, 0.35-0.45% carbomer, 2-3% sodium carboxymethyl cellulose, 0.8-1.2% gelatin, 0.4-0.5% sodium hyaluronate, 1.0-1.4% bentonite, 30-32% glycerol, 2-5% polyethylene glycol, 0.9-1.1% aluminum glycolate, 1.5-1.7% disodium edetate, and the content is made up to 100% with deionized water.
2. The hydrogel preparation according to claim 1, characterized in that The components of the hydrogel preparation are: 7% sodium polyacrylate NP700, 0.45% carbomer, 3% sodium carboxymethyl cellulose, 1.2% gelatin, 0.4% sodium hyaluronate, 1.2% bentonite, 30% glycerol, 3% polyethylene glycol, 1.1% aluminum glycolate, 1.6% disodium edetate, and deionized water is supplemented to 100%.
3. The hydrogel preparation according to claim 1, characterized in that The hydrogel preparation also includes a transdermal short peptide Ser-Cys-Arg.
4. The hydrogel preparation according to claim 3, characterized in that The content of the transdermal short peptide in the hydrogel preparation is 0.08%.
5. The method for preparing the hydrogel preparation according to claim 1 or 2, characterized in that: The steps include: Sodium polyacrylate NP700, sodium carboxymethyl cellulose and carbomer are dispersed in an appropriate amount of glycerol, and then deionized water is added and stirred at 50±2°C to obtain colloid liquid A; then the remaining glycerol, sodium hyaluronate, gelatin, polyethylene glycol, bentonite and aluminum glycolate are added to the above colloid liquid A in sequence, and the suspension B is obtained after stirring; after the suspension B is stable, disodium ethylenediaminetetraacetate is added; and the pH of the obtained paste matrix is adjusted to 6.5±0.1 with triethanolamine, and the mixture is aged in a constant temperature box at 40±2°C for 20-30min, and then placed at room temperature for 40-50h to obtain the finished product.
6. The method for preparing the hydrogel preparation according to claim 3 or 4, characterized in that: The steps include: Sodium polyacrylate NP700, sodium carboxymethyl cellulose and carbomer are dispersed in an appropriate amount of glycerol, and then deionized water is added, and the mixture is stirred evenly at 50±2°C to obtain colloid liquid A; then the remaining glycerol, sodium hyaluronate, gelatin, polyethylene glycol, bentonite and aluminum glycolate are added to the above colloid liquid A in sequence, and the mixture is stirred evenly to obtain suspension B; after the suspension B is stable, disodium ethylenediaminetetraacetic acid is added; transdermal short peptides are added under low-speed stirring, and the pH of the obtained paste matrix is adjusted to 6.5±0.1 with triethanolamine, and the mixture is aged in a constant temperature box at 40±2°C for 20-30min, and then placed at room temperature for 40-50h to obtain the finished product.
7. Use of the hydrogel preparation according to any one of claims 1 to 4 in the preparation of cosmetic products.
8. The use according to claim 7, characterized in that The beauty products include skin care products and cosmetics.
9. Use of the hydrogel preparation according to any one of claims 1 to 4 in the preparation of drug-carrying transdermal products.
10. The use according to claim 9, characterized in that The drug-carrying transdermal product also contains at least one active drug ingredient in an effective dose for treating a disease.